Boundary conditions for Onboard thermal-management system of a battery pack under ultrafast charging. (15th March 2022) - Wu, Xiaogang; Du, Jiuyu; Guo, Haoqi; Qi, Mingshan; Hu, Fangfang; Shchurov, N.I.
Abstract: Ultrafast charging of lithium-ion batteries for electric vehicles has been recognized as a promising technology to shorten charging time. However, ultrafast charging can lead to rapid heat-generation in the battery pack, resulting in excessive temperature and serious deterioration in temperature consistency. The purpose of this study is to determine the boundary conditions of the influencing factors on a battery liquid-cooling system under ultrafast charging. In this study, the thermal behavior of a battery pack during ultrafast charging is analyzed by identifying the battery parameters. A liquid-cooling system is designed to verify the boundary-condition optimization of the temperature-changing influencing factors. Finally, the results show that the cooling-system using the boundary conditions can well restrain the maximum temperature to within 45 °C and the temperature difference to within 2 °C in the pack under an ultrafast charging condition. Highlights: The thermal behavior of a battery pack during ultrafast charging is analyzed. A liquid cooling system for high specific energy battery module is established. The boundary conditions on liquid-cooling system are determined. Different liquid-cooling systems under ultrafast charging are evaluated.